Effects of methamphetamine on locomotor activity and thalamic gene expression in leptin-deficient obese mice - Gonzalez, Betina (2017)
Leptin is an adipose-derived hormone that regulates energy balance. Leptin receptors are expressed in extrahypothalamic sites and several reports showed that leptin can influence feeding and locomotor behavior via direct actions on dopaminergic neurons. The leptin deficient mouse (ob/ob) has been used as an animal model of blunted leptin action, and presents with obesity and mild type 2 diabetes. We used ob/ob mice to study the effect of repeated 7-day methamphetamine (METH) administration analyzing locomotion, behavioral sensitization, and somatosensory thalamic mRNA expression of voltage-gated calcium channels and glutamatergic receptors using RT-PCR. We observed reduced METH-mediated responses in ob/ob mice associated with enhanced in mRNA expression of key voltage-gated and glutamate receptors in the somatosensory thalamus. Results described here are important for understanding the control of locomotion and thalamocortical excitability by leptin.